Has Science Displaced the Soul? Debating Love and Happiness. - Sharpe, Kevin; Bryant, Rebecca Bryant (Lanham : Rowman & Littlefield Publishers, 2005)
Can science explain powerful human emotions such as love and happiness? Or, are these emotions something more than the action of biochemicals and electrical impulses? Science is constantly uncovering the mysteries of our nature, but we are uneasy about submitting our most intimate feelings to its scrutiny. Unflinching in facing these issues, Kevin Sharpe provides a clear and current summary of the discoveries of science and what our spiritual lives still have to offer in the ongoing effort to understand our deepest urges. In the 21st century, is it necessary to discard our traditional beliefs.
Interlude 5: Happiness, Love, and the DivineNotes; Bibliography; Index; About the Authors
Description based upon print version of record.
Keywords: Evolutionary psychology; Happiness -- Religious aspects; Love -- Religious aspects; Psychology and religion; Happiness -- Religious aspects; Love -- Religious aspects; Psychology and religion; Evolutionary psychology; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; RELIGION / Theology; Electronic books